Implications of Local Knowledge Construction in Empowerment Practices of Women's Groups at Batik Liza Mangrove Studio, Pematang Johar Village, Deli Serdang Regency - Mujahiddin Mujahiddin; Yurisna Tanjung; Nurhasanah Nasution (Budapest International Research and Critics University, 2021)
At present, the global development goals stated in the Sustainable Development Gols (SDGs), the empowerment agenda is still the main focus, especially with regard to empowering women's groups. Although it does not explicitly emphasize women's empowerment in it, in many cases community empowerment practices through ADD always place poor and under-prosperous women as the main participants. In Pematang Johar Village, Deli Serdang Regency, the practice of empowering women's groups is carried out by developing entrepreneurship based on the local potential of the village, namely through batik crafts. This program begins with the formation of a women's batik group with the aim that the batik group formed can produce batik works with local characteristics which are then given the name